IS LANGUAGE NATURAL? - Endang Yuliani Rahayu (Universitas Stikubank (UNISBANK) Semarang, 2012)
Is language natural? We may think of this from the point of view of philosophy of language. Based on the philosophy of language, natural language is similar to ordinary language. Natural language is different from constructed languages and formal languages such as computer-programming languages or the languages used in the study of formal logic, especially mathematical language. We may say that natural language is any languages which arouse in unpremeditated fashion as the result of the innate facility for language possessed by the human intellect. Key words: natural language, philosophy of language, constructed language, formal language